Genesis and pore evolution of dolomite reservoir in the Majiagou Formation, Ordos Basin, China. Issue 1 (January 2022) - Wang, Baobao; Tan, Xiucheng; Su, Wenjie; Yan, Wei; Xiao, Di; Guo, Mushi; Zhong, Shoukang; Xu, Yuqing; Yang, Mengying
In gypsum–carbonate rock assemblages, multistage and complex fluids control the formation of dolomite reservoirs that are a focus of hydrocarbon exploration. It is difficult to determine the types of dolomite reservoirs and their formation mechanisms due to the diverse rock assemblages and multiple stages of diagenesis. In this study, we investigated the petrology, reservoir physical properties, and geochemistry of the 6th sub-member of member five of the Majiagou Formation (i.e. Ma5 6 ) in the Ordos Basin, China. These data were used to determine the nature and types of gypsum–carbonate rocks, and constrain their reservoir characteristics and diagenetic history, and fluid-related mechanisms that led to dolomite reservoir development and preservation. The Ma5 6 was deposited on a restricted evaporatic platform in the North China Craton, and contains three main types of dolomite reservoirs with variable types of reservoir space. Dolomite reservoir formation was closely related to penecontemporaneous dolomitization, karstification, and differential cementation. Early large-scale dolomitization produced dolomitized carbonate sediments that were resistant to compaction and dissolution, which was conducive to the preservation of primary and secondary pores. The intermittent exposure and dissolution of mound–shoal facies sediments, due to high-frequency sea-level fluctuations, was the dominant mechanism for formation of secondary dissolved pores and high-quality reservoirs. During burial, differential cementation occurred due to interaction between fluids and pore size, which determined the extent of reservoir preservation. In general, the studied dolomite reservoirs have undergone multistage diagenesis and alteration, which led to complex and multistage development of the reservoir porosity. However, the reservoir lithology and pore space developed mostly in the depositional to penecontemporaneous stages. Our results provide new insights into the origins of deeply buried dolomite reservoirs in carbonate–evaporite successions.